2014
DOI: 10.1177/0145721714521872
|View full text |Cite
|
Sign up to set email alerts
|

Health, Community, and Spirituality

Abstract: Evaluation results show FFF's success at engaging overweight adults in behavior changes related to healthy eating and exercise. FFF demonstrates the potential of faith-based health interventions to address obesity and diabetes risk in high-need communities of color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…The current findings and those from other studies suggest that greater specificity in the measurement of religion and religious practices may be needed to understand when R/S can be protective or destructive toward maintaining good health habits. As well, faith based and faith placed interventions may be more successful at incorporating elements from specific faiths that can help members change their health habits in the context of that faith (Fitzgibbon et al, 2005, Gutierrez et al, 2014, Wilcox et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The current findings and those from other studies suggest that greater specificity in the measurement of religion and religious practices may be needed to understand when R/S can be protective or destructive toward maintaining good health habits. As well, faith based and faith placed interventions may be more successful at incorporating elements from specific faiths that can help members change their health habits in the context of that faith (Fitzgibbon et al, 2005, Gutierrez et al, 2014, Wilcox et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is preventable through dietary changes and weight loss, increased physical activity, and other lifestyle changes [10,11], and in addition to lowering clinical measurements such as weight and glucose [11,12,13,14,15,16,17,18,19,20,21,22,23], community-based interventions modeled after the DPP have also been shown to promote health benefits such as improved nutrition and increased exercise [12,13,15,22,23,24,25,26,27,28]. DPP studies that have been translated into community settings have included various modifications to the original DPP protocol in order to address feasibility and sustainability challenges associated with the program, and to address the specific needs of the target communities in which studies are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…All studies measured participant weight; nine reported a statistically significant reduction in mean weight post-intervention or for the intervention group compared with controls. 1517,19,2226 Five RCTs were included among these 16,19,22,24,25 ; all five reported statistically significant weight loss in intervention versus control participants. Effect sizes for changes in weight were small, however, ranging from 0.01 to 0.32.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In fact, it is unclear whether any single measurement of diet or physical activity was utilized across more than one study. Seven studies examined changes in physical activity, all measured by participant self-report, 15,18,2124,26 with some utilizing validated, reliable measures for Hispanic populations (e.g., Global Physical Activity Questionnaire, International Physical Activity Questionnaire, Rapid Assessment of Physical Activity) and others employing study-specific individual physical activity items. Four studies reported significant changes in physical activity levels post-intervention 15,18,23,26 (Appendix Table 1).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation